Analysis and determination of factors associated with student performance based on composite assessment scores - Bahrom, Suhaila; Hisham, Balqis (Universiti Islam Selangor, 2024)
Examining final scores among pre-university engineering students is crucial for understanding their academic performance and identifying factors contributing to success or challenge in their educational journey. These scores are pivotal indicators of students' grasp of fundamental engineering principles and readiness for higher education. This study examines the correlation between different course assessments and final exam scores in a Mathematics course for pre-university engineering students. A dataset comprising assessments such as quizzes, open-book tests, and tutorials was collected from 552 pre-university engineering students at the Centre for Foundation Studies, International Islamic University Malaysia, for the 2023/2024 cohort. Regression analysis was employed to identify the significance course assessments, which were carried out using Python. The study revealed that all the quizzes, including open book test 2 and open book test 3, are significantly correlated with final examination scores with an adjusted R-squared of 0.467. This value indicates that 46.7% of the variation in final examination scores can be predicted by combining all quizzes and two open-book tests. This study examines the effectiveness of course assessments in predicting the final examination performance of students in pre university engineering programs. Furthermore, it presents valuable recommendations for enhancing assessment strategies to support and foster student achievement more effectively.